Pengaruh Teknologi Wearable Devices Virtual Reality terhadap Motivasi Belajar Siswa pada Mata Pelajaran Sejarah Kelas XI SMA Negeri 16 Bone - Ika Sulistiawati; Andi Kasmawati; Muldiyana Muldiyana (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Students' motivation to learn decreases if they feel bored with the same learning cycle, the conventional way of delivering material in some subjects is not interesting for students, one of which is history. When learning history, students' learning motivation tends to decrease, because it is theoretical and therefore considered boring. Learning history with conventional methods makes students feel bored and inactive in learning, therefore it is necessary to apply technology as a medium in the learning process in the classroom. This study aims to determine the effect of the use of virtual reality wearable devices technology on students' learning motivation in history subjects. The use of Virtual Reality wearable devices technology is an appropriate medium in history subjects because it can display audio visuals in 3D form which allows students to increase situational awareness and expand their vision. The use of Virtual Reality in learning allows students to engage in a more in-depth and interactive learning experience so that students' learning motivation increases and makes it easier to understand the material presented. A more immersive and realistic learning experience can make the subject matter more interesting and enjoyable. The study uses quantitative research methods. The results of this study indicate that the use of virtual reality in history learning can affect students' learning motivation. This can be seen from the results of the hypothesis test that the t-count value > t-table or 15,819 > 2.051 and the sig value of 0.001 < 0.05. Therefore, it can be concluded that H1 is accepted and H0 is rejected.